2019
DOI: 10.1108/jgm-12-2018-0060
|View full text |Cite
|
Sign up to set email alerts
|

Expatriate time to proficiency: individual antecedents and the moderating effect of home country

Abstract: Purpose The purpose of this paper is to examine the direct impact of individual variables (cultural openness, social orientation, willingness to communicate, confidence in own technical abilities, active stress resistance, prior international experience) on expatriate time to proficiency (TTP); and the moderating effects of the home country on the relationships between these individual variables and expatriate TTP. Design/methodology/approach The authors use a quantitative, self-administered questionnaire to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 68 publications
(129 reference statements)
3
25
0
Order By: Relevance
“…Do SIEs in different countries adjust differently (Waxin and Brewster, 2020)? What are the individual, organisational and contextual factors that reduce the different types of SIEs' job performance and time to proficiency (Waxin et al, 2019;Waxin et al, 2016;Lessle et al, 2021)?…”
Section: Sies' Adjustment To the New Countrymentioning
confidence: 99%
“…Do SIEs in different countries adjust differently (Waxin and Brewster, 2020)? What are the individual, organisational and contextual factors that reduce the different types of SIEs' job performance and time to proficiency (Waxin et al, 2019;Waxin et al, 2016;Lessle et al, 2021)?…”
Section: Sies' Adjustment To the New Countrymentioning
confidence: 99%
“…Many researchers have examined the individual characteristics of expatriates that predict success in the assignment: these include job factors, personal traits (flexibility/ tolerance for ambiguity, self-efficacy), relational abilities/ cross cultural competencies, motivational state, language skills, family situation, (Anderson, 2005;Reiche, Harzing & Kraimer, 2009;Waxin, Brewster & Ashill, 2019), and previous international work experience (Caligiuri, Tarique & Jacobs, 2009;Culpan & Wright, 2002;Kim, Brewster & Chung, 2019). These criteria have been found to be critically related to expatriate performance in international assignments and their consideration depends on the role of the expatriates (Tungli & Peiperl, 2009) and the expatriates' country of origin (Waxin et al, 2019).…”
Section: Expatriate Selection Criteriamentioning
confidence: 99%
“…Job-related selection criteria are based on the international assignment's job description and competency profile and knowledge, skills and competencies necessary to perform the job role (Waxin, 2008a;Waxin 2008b;Avril & Magnini, 2007). Confidence in technical skills has been found to predict work adjustment and reduce expatriates' time to proficiency (Bhaskar-Shrinivas et al, 2005;Waxin, 2003, Waxin et al, 2019, and previous international experience to predict expatriates' success (Caligiuri et al, 2009). Green (2012), focusing on American expatriate officials, found that the length of previous international experience was positively related to adjustment scores.…”
Section: Expatriate Selection Criteriamentioning
confidence: 99%
See 2 more Smart Citations